Automated Measurement Device / Nina Syahira Shahman - Shahman, Nina Syahira (2020)
As many years passed by, fashion become one of the must follow trends, thus demands increase and taking measurement in manual way by using measuring tape will slow down the process. Nowadays, everything are based on technology. Our RaSP Company have new product to introduce to the consumers which is Automated Measurement Device. Our company is targeting in supply for this product since it is customer-friendly which helps in saving time and avoid measurement error especially to consumers that love to buy everything online. Therefore, Automated Measurement Device can help the consumer because the products are affordable and easy to use. Overall marketing strategy will be included specific marketing philosophy and strategy of the company, the value chain and the channel of distribution in the target market. First of all, our target market involve mass customers basically those that have business in clothing line which are online shoppers, fashion designers, tailors and boutique owners. The product is not only designed to save time for people that are always busy but to minimize error for body measurement. The price is reasonable and there is no physical energy used. Our company target for production in 2nd year we will target to increase it by RM 1 500,000. The management team in our company consist of several sections and is conducted by experienced employee to make sure our company is run efficiently.